Functional traits mediate individualistic species‐environment distributions at broad spatial scales while fine‐scale species associations remain unpredictable. Issue 12 (28th November 2022) - Beck, Jared J.; Li, Daijiang; Johnson, Sarah E.; Rogers, David; Cameron, Kenneth M.; Sytsma, Kenneth J.; Givnish, Thomas J.; Waller, Donald M.
Abstract: Premise: Numerous processes influence plant distributions and co‐occurrence patterns, including ecological sorting, limiting similarity, and stochastic effects. To discriminate among these processes and determine the spatial scales at which they operate, we investigated how functional traits and phylogenetic relatedness influence the distribution of temperate forest herbs. Methods: We surveyed understory plant communities across 257 forest stands in Wisconsin and Michigan (USA) and applied Bayesian phylogenetic linear mixed‐effects models (PGLMMs) to quantify how functional traits and phylogenetic relatedness influence the environmental distribution of 139 herbaceous plant species along broad edaphic, climatic, and light gradients. These models also allowed us to test how functional and phylogenetic similarity affect species co‐occurrence within microsites. Results: Leaf height, specific leaf area, and seed mass all influenced individualistic plant distributions along landscape‐scale gradients in soil texture, soil fertility, light availability, and climate. In contrast, phylogenetic relationships did not consistently predict species‐environment relationships. Neither functionally similar nor phylogenetically related herbs segregated among microsites within forest stands. Conclusions: Trait‐mediated ecological sorting appears to drive temperate‐forest community assembly, generating individualistic plant distributions along regional environmental gradients. This finding links classic studies in plant ecology and prior research in plant physiological ecology to current trait‐based approaches in community ecology. However, our results fail to support the common assumption that limiting similarity governs local plant co‐occurrences. Strong ecological sorting among forest stands coupled with stochastic fine‐scale interactions among species appear to weaken deterministic, niche‐based assembly processes at local scales.